An alternative wheel regenerative mechanism in surface grinding: distributed grit dullness captured by specific energy waves. (1st January 2022) - Tóth, Máté; Sims, Neil D.; Curtis, David
Highlights: The effect of distributed grit dullness on grinding stability is presented. Contrary to the general consensus of the literature, stable parameter domains are predicted. Extensive surface grinding experiments demonstrate the validity of the theoretical predictions. The results are discussed with regard to further academic research and their applicability to industrial practice. Abstract: Regenerative chatter is a serious problem in machining. It is an unstable relative vibration between the workpiece and the cutting tool that adversely affects virtually all chip formation processes. This paper addresses regenerative chatter in grinding, which is one of the most widely used abrasive processes today. As a result of significant tool wear in grinding, surface regeneration (which is a prerequisite for regenerative chatter) can occur not only on the workpiece but also on the grinding wheel. This article is concerned with the regenerative mechanism by which wheel-related instability develops. In the present study, the role of distributed grit dullness alone is explored. A new chatter model is formulated and validated by both numerical simulations and experimental data. The new theory accurately predicts the existence of stable regimes in grinding, for the first time. This is in contrast to the published literature where the consensus has been that grinding cannot be stable with respect to wheel regeneration. Consequently, the present contribution enables a novel opportunity to increase the productivity of industrial grinding operations.